Has Digitalisation Mitigated the Impact of Covid-19 on the Manufacturing Sector’s Performance? - Tien-Ming Yip; Wee-Yeap Lau; Shankaran Nambiar (Australasian Accounting, Business and Finance Journal, 2023)
The Covid-19 pandemic brought many businesses to a standstill as international travel restriction was imposed across countries in addition to a national lockdown. Firm performances were depressed due to reduced order and output. This study examines whether digitalisation has mitigated the negative impact of the Covid-19 pandemic on Malaysia's manufacturing sector. Using sales as the performance yardstick of 24 industrial sectors from January to December 2020, our result shows that manufacturing sales performance was negatively related to the Covid-19 pandemic. However, the adverse impact of Covid-19 was mitigated with a higher level of digitalisation. The mitigating role of digitalisation remains robust in further analysis. This study has managed to quantify the mitigating effect of Covid-19 on manufacturing sectors. As a policy implication, the government should expedite the introduction of the 5G network, promote digital adoption across all sectors to ensure business continuity and provide an effective response mechanism in any pandemic or crisis.
Keywords: Covid-19 pandemic; Digitalization; Mitigating effect; Manufacturing sales; Malaysia